PENGGESERAN TANGGUNG JAWAB TINDAK HUKUM ADMINISTRASI KE TINDAK PIDANA KORUPSI DALAM KASUS DISKRESI HUKUM PEJABAT TATA USAHA - Marcus Lukman (Perspektif, 2005)
Administrative Legal Action by Administrative Official which is on based in discretionary power can not always be shifted to become the criminal law responsibility. Because each the law area owning justification value in with the concept and its legal norm. Although, an action of "discretionary power" from the aspect of its legal norm impress to represent as illegal action, however from its goal exactly give the benefit and the more positive law justice value. So that cannot categorized as corruption.